Oil Bioremediation in a Tropical Contaminated Soil Using a Reactor - TREJOS-DELGADO,CATALINA (2020)
Abstract This research was implemented in the Colombian Amazon forest area; to assess the effect of Tween-80® surfactant in the degradation of the Total Petroleum Hydrocarbons (TPH) in bioremediation treatments under aerobic conditions in the laboratory and pilot-scale. One control treatment, Natural Attenuation (AT) and four biostimulation treatments with leonardite with four different dosages of Tween-80® were proposed. The efficacy of organic stimulators and nonionic surfactant in soil microbiota was studied at laboratory and pilot scales, the latter in a passive aeration reactor. The test that presented a better performance was carried out with a Convective Flow Reactor (CFR) at pilot-scale. The results showed that bioremediation strategies improved the natural degradation process; the best outcomes were obtained in a treatment that includes Leonardite and Tween-80® (1.5 g/L) with 52% TPH degradation in 80 days (d).Tween-80® produced an effect in TPH solubility, and increased the production of CO2 in distinctive bioremediation treatments in both periods. The kinetics of CO2 production showed that the system required a periodic addition of a co-substrate as well as an increase of soil microbiota through the addition of compost (pilot scale). In this stage more than 76% of contaminant was degraded in 60d.